PENDIDIKAN AGAMA ISLAM (PAI) PADA ANAK USIA DINI DI RAUDHATUL ATHFAL (RA) DARUL HUDA MATARAM BARU LAMPUNG TIMUR - daman, Damanhuri; Jamiluddin Yacub; Nur Indahsari; Ermanita Permatasari (LPPM STAI DARUSSALAM LAMPUNG, 2021)
PAI learning in early childhood still shows various problems that are less encouraging. The learning process of Islamic Education is only limited to the process of transfer of knowledge of Islamic Religion so that it is less able to convert it into